2017
DOI: 10.1111/jgs.14870
|View full text |Cite|
|
Sign up to set email alerts
|

Common Drug Side Effects and Drug‐Drug Interactions in Elderly Adults in Primary Care

Abstract: Prescribing medications, recognizing and managing medication side effects and drug interactions, and avoiding polypharmacy are all essential skills in the care of older adults in primary care. Important side effects of medications commonly prescribed in older adults (statins, proton pump inhibitors, trimethoprim-sulfamethoxazole and fluoroquinolone antibiotics, zolpidem, nonsteroidal antiinflammatory drugs, selective serotonin reuptake inhibitors, dipeptidyl peptidase 4 inhibitors) were reviewed. Important dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 46 publications
0
10
1
2
Order By: Relevance
“…Of the most commonly used prescription and over-the-counter drugs in the US for older adults [64], many are known to cause mitochondrial toxicity such as the cholesterol lowering drugs (Zocor, Lipitor, Pravacol, Crestor), pain medication (Aspirin, Tylenol, Aleve) and heartburn medication (Prilosec). Table 2 lists references for mitochondrial dysfunction reported for these prescription and over-the-counter (OTC) medications.…”
Section: Polypharmacy In the Geriatric Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the most commonly used prescription and over-the-counter drugs in the US for older adults [64], many are known to cause mitochondrial toxicity such as the cholesterol lowering drugs (Zocor, Lipitor, Pravacol, Crestor), pain medication (Aspirin, Tylenol, Aleve) and heartburn medication (Prilosec). Table 2 lists references for mitochondrial dysfunction reported for these prescription and over-the-counter (OTC) medications.…”
Section: Polypharmacy In the Geriatric Populationmentioning
confidence: 99%
“…It has been reported that elderly patients taking cholesterol lowering drugs (Zocor, Lipitor, etc.) have shown drug–drug interactions (DDI), particularly with the anti-lipidemic drug Lopid (gemfibrozil [53,106]), but also with certain antibiotic classes, such as macrolides [107,108] and fluoroquinolones [109,110] and the heart medication, Nexteron (amiodarone) [64,111]. All of these drugs have been shown to cause mitochondrial toxicity by targeting a variety of, as well as multiple, mitochondrial mechanisms/targets.…”
Section: Polypharmacy In the Geriatric Populationmentioning
confidence: 99%
“…Polypharmacy, defi ned as taking more than 5 medications, is associated with an increased risk of adverse drug events, falls, fractures, decreased adherence, and "prescribing cascade"-prescribing more drugs to treat side effects of the fi rst drug (eg, adding hypertensive medications to treat hypertension induced by If a statin will be the 20th pill, it may be less benefi cial than if it is the fi fth pill ORKABY AND COLLEAGUES nonsteroidal anti-infl ammatory drugs). 60 This is particularly important when considering adding additional medications. If a statin will be the 20th pill, it may be less benefi cial and more likely to lead to additional adverse effects than if it is the fi fth medication.…”
Section: ■ Special Considerationsmentioning
confidence: 99%
“…A full list of interactions can be found in resources, such as the Australian Medicines Handbook [ 21 ] but the cardiovascular drugs known to interact with warfarin include amiodarone, fibrates, and statins. Statins and warfarin are amongst the most commonly prescribed prescription medications and may be involved in both pharmacokinetic interactions and an increased risk of adverse effects [ 22 ]. However, there have been conflicting reports on the risks associated with this combination, particularly regarding warfarin control and bleed risk.…”
Section: Discussionmentioning
confidence: 99%